Development Needs Analysis of Child Literacy Based on Multimodal Technology - Mclean HY; Muhammad Aswad (Vifada Journal of Education, 2026)
Purpose: This study aims to analyze the current condition of children's literacy and identify the needs for developing multimodal technology-based literacy in North Konawe Regency, Indonesia. Research Design and Methodology: A descriptive qualitative approach was employed involving elementary school students, teachers, and school stakeholders. Data were collected through questionnaires, semi-structured interviews, observations, and document analysis, and were analyzed using descriptive analysis, thematic analysis, and SWOT analysis to identify strategic priorities for literacy development. Findings and Discussion: The findings indicate that although students generally demonstrate positive reading interest, literacy development is constrained by limited reading resources, inadequate technological infrastructure, uneven internet access, insufficient teacher competence in digital pedagogy, and limited locally relevant digital learning materials. The SWOT analysis reveals considerable opportunities for strengthening literacy through multimodal technology, particularly by improving infrastructure, teacher capacity, curriculum integration, and collaboration among educational stakeholders. Implications: The findings provide evidence-based recommendations for policymakers, schools, and educators to design sustainable multimodal literacy programs that enhance children's literacy competencies while supporting digital transformation in primary education. Future studies are encouraged to evaluate the effectiveness of multimodal literacy interventions across broader educational contexts.